2022
DOI: 10.1136/bmjopen-2022-062685
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial using Coronary Artery Calcium Scoring in Australian Women with Novel Cardiovascular Risk Factors (CAC-WOMEN Trial): study protocol

Abstract: IntroductionCardiovascular disease (CVD) is the leading cause of death in women around the world. Aboriginal and Torres Strait Islander women (Australian Indigenous women) have a high burden of CVD, occurring on average 10–20 years earlier than non-Indigenous women. Traditional risk prediction tools (eg, Framingham) underpredict CVD risk in women and Indigenous people and do not consider female-specific ‘risk-enhancers’ such as hypertensive disorders of pregnancy (HDP), gestational diabetes mellitus (GDM) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“… 66 More recently, small pilot studies have shown feasibility and acceptability of web‐based CVD prevention and physical exercise interventions, 64 , 65 but require confirmation in larger studies. Box 2 details these studies 64 , 65 , 66 and Box 3 highlights other ongoing larger RCTs, 70 including the innovative multisite CAC‐Women Trial ( N = 700) 69 currently underway which will target women with at least one risk‐enhancing factor of HDP, gestational diabetes and/or premature menopause. Computed tomography coronary artery calcium scoring will identify women with premature subclinical atherosclerosis and guide risk factor counselling.…”
Section: Cardiovascular Risk Reduction After Pregnancymentioning
confidence: 99%
“… 66 More recently, small pilot studies have shown feasibility and acceptability of web‐based CVD prevention and physical exercise interventions, 64 , 65 but require confirmation in larger studies. Box 2 details these studies 64 , 65 , 66 and Box 3 highlights other ongoing larger RCTs, 70 including the innovative multisite CAC‐Women Trial ( N = 700) 69 currently underway which will target women with at least one risk‐enhancing factor of HDP, gestational diabetes and/or premature menopause. Computed tomography coronary artery calcium scoring will identify women with premature subclinical atherosclerosis and guide risk factor counselling.…”
Section: Cardiovascular Risk Reduction After Pregnancymentioning
confidence: 99%